Association between haptoglobin polymorphism and coronary artery disease: a meta-analysis - Wang, Jiao; Zhou, Xiaokai; Su, Yue; Chai, Dongjian; Ruan, Yaoyao; Wang, Jinhua (Frontiers in Genetics, 2024)
Background Previous studies have investigated the association between the haptoglobin rs72294371 polymorphism and coronary artery disease (CAD) risk, but the results are controversial and uncertain. Therefore, this study aimed to systematically review the literature on haptoglobin polymorphism and susceptibility to CAD. Methods PubMed, Embase, Web of Science, Cochrane Library, and Wanfang databases were used to identify relevant studies from their inception to April 2024. The pooled odds ratio (OR) with corresponding 95 % confidence interval (CI) were used to assess the strength of the association. An OR value greater than one suggested an increased risk; otherwise, it suggested a protective risk.Results A total of 15 studies comprising 8632 individuals (2988 cases and 5644 controls) were included. In the current meta-analysis, a significant association between haptoglobin polymorphism and CAD was found under recessive model (OR:0.74, 95% CI:0.60-0.92), dominant model (OR: 0.82, 95% CI: 0.71-0.95), homozygote model (OR: 0.70, 95% CI: 0.53-0.92), and allelic genetic model (OR: 0.80, 95% CI: 0.69-0.94). In the analysis stratified by ethnicity, a statistically significant association was observed in Asians rather than Caucasian population.This meta-analysis indicates that haptoglobin polymorphism is associated with CAD susceptibility, especially in Asians.